The alternative sigma factor SigN of Bacillus subtilis is intrinsically toxic - Burton, Aisha T; Pospíšilová, Debora; Sudzinova, Petra; Snider, Elizabeth V; Burrage, Andrew M; Krásný, Libor; Kearns, Daniel B (Journal of bacteriology, 2023)
Sigma factors bind and direct the RNA polymerase core to specific promoter sequences, and alternative sigma factors direct transcription of different regulons of genes. Here, we study the pBS32 plasmid-encoded sigma factor SigN of Bacillus subtilis to determine how it contributes to DNA damage-induced cell death. We find that SigN causes cell death when expressed at high levels and does so in the absence of its regulon suggesting it is intrinsically toxic. One way toxicity was relieved was by curing the pBS32 plasmid, which eliminated a positive feedback loop that led to SigN hyper-accumulation. Another way toxicity was relieved was through mutating the chromosomally encoded transcriptional repressor protein AbrB, thereby derepressing a potent antisense transcript that antagonized SigN expression. SigN efficiently competed with the vegetative sigma factor SigA in vitro, and SigN accumulation in the absence of positive feedback reduced SigA-dependent transcription suggesting that toxicity may be due to competitive inhibition of one or more essential transcripts. Why B. subtilis encodes a toxic sigma factor is unclear but SigN may function in host-inhibition during lytic conversion, as phage lysogen genes are also encoded on pBS32. IMPORTANCE Alternative sigma factors activate entire regulons of genes to improve viability in response to environmental stimuli. The pBS32 plasmid-encoded alternative sigma factor SigN of Bacillus subtilis however, is activated by the DNA damage response and leads to cellular demise. Here we find that SigN impairs viability by hyper-accumulating and outcompeting the vegetative sigma factor for the RNA polymerase core. Why B. subtilis retains a plasmid with a deleterious alternative sigma factor is unknown.
Keywords: genetická transkripce; Immunoglobulin A, Secretory; Bacillus subtilis; DNA-Directed RNA Polymerases; sigma faktor; Transcription, Genetic; Sigma Factor; pBS32; bakteriální proteiny; regulace genové exprese u bakterií; cell death; prophage; imunoglobulin A sekreční; Gene Expression Regulation, Bacterial; Bacterial Proteins; SigN; AbrB; plasmid; DNA řízené RNA-polymerasy